Video Equipment and Video Shot Composition - Ricky Telg (EDIS)
You should become as familiar as possible with the video camera you plan to use and how best to use it in creating effective video shots. For a basic video shoot, the minimum equipment requirements are a video camera, a microphone, a light source, and a tripod. Composition refers to the types of video shots you will shoot. This 5-page fact sheet provides an overview of equipment and composition techniques. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.